Association of kinesiophobia with pain sensitization and severity in knee osteoarthritis patients with chronic pain - Zahraa Nour Eldine Ismail; Mohamed Ahmed Hefny; Ahmed Elarabi Hendi; Maha A. Abdel Fattah (Egyptian Rheumatology and Rehabilitation)
Abstract Background Physical activity is beneficial for chronic musculoskeletal painful conditions as it improves muscle strength, joint support, and stability. Kinesiophobia, the fear of movement, is prevalent in these conditions due to the feeling of vulnerability to reinjury and pain. So, it can influence the severity and chronicity of pain. The aim of this study was to assess the association of kinesiophobia with pain sensitization and severity in knee osteoarthritis (OA) patients with chronic pain. Results Our participants were 175 patients with knee OA and chronic pain with a mean age of 50.58 ± 7.35; most of them were females (111 females versus 64 males). Fifty-one (29.1%) participants had a high kinesiophobia degree on the Tampa scale for kinesiophobia (TSK). Age had a positive correlation with kinesiophobia severity (TSK and the Falls Efficacy Scale International (FES-I)) (P = 0.013 and P = 0.01, respectively). The knee OA duration, pain severity, central sensitization inventory (CSI), and conditioned pain modulation (CPM) had a positive correlation with kinesiophobia (TSK and FES-I) (P = 0.0001). The electrical pain threshold and the pain pressure threshold were negatively correlated with TSK and FES-I (P = 0.0001). In multiple linear regression analysis, CSI was a significant predictor for TSK (P = 0.001), and CSI and CPM were significant predictors for FES-I (P = 0.001 and P = 0.007, respectively). Conclusion There is a significant association between kinesiophobia and pain sensitization and severity in knee OA patients, so a graduated exercise program and considering kinesiophobia assessment and management is essential in knee OA rehabilitation.